Discrimination Between the Pressure and Temperature Effects of an FBGTaper Sensor Using a Tapered Fiber Sensor - Zahin, Hameedullah (Journal of Natural Sciences – Kabul University, 2023)
Fiber Bragg Grating in Tapered Fiber (FBGTaper) sensors have become widely used in the industry for diagnosing the safety of mechanical structures due to their high sensitivity, immunity to electromagnetic interference, linearity, and lightness. One limitation of FBGTaper sensors is their inability to distinguish the effects of temperature and pressure during simultaneous measurements. To address this, a solution is proposed by designing a tapered fiber-FBG composite sensor. The studies conducted on the designed composite sensor show that there is no sensitivity interference between temperature and pressure. In the composite sensor, a tapered fiber optic sensor provides a temperature sensitivity of −932.8 pm/°C, and the FBGTaper sensor offers a combined temperature sensitivity of 8.62 pm/°C and pressure sensitivity of 5.77 pm/MPa.